Description Of Public Knowledge About The Covid-19 Pandemic In Semakata Medan 2020 - Mardiati Barus; Helinida Saragih; Ernasari Sinurat (Jurnal EduHealth, 2023)
Covid-19isan emerging respiratory disease caused by the coronavirus. This disease is highly contagious, and its main symptoms include fever, dry cough, fatigue, myalgias, and dyspnea. Therefore, people need knowledge about Covid-19 and understand how to deal with this disease. The purpose of this study was to find out the description of public knowledge about the Covid 19 pandemic in Sempakata Village. The research design used was a correlational design with a cross sectional approach. This research was conducted in Sempakata Village. The number of samples in this study were 91 people using the total sampling technique. The results of this study obtained data that the community's knowledge about Covid -19, namely knowledge in the good category was 56 people (61.5%) and knowledge in the sufficient category was 35 people (38.5%). so that it can be said that the public's knowledge of Covid-19 is good.